Gemeinschaft in the midst of Gesellschaft? Love as an organizational virtue. Issue 1 (2nd January 2017) - Cunha, Miguel Pina e; Clegg, Stewart R.; Costa, Cláudia; Leite, António Pinto; Rego, Arménio; Simpson, Ace Volkmann; Sousa, Marta Oom de; Sousa, Milton
Abstract: Love is a powerful human process that has attracted the attention of scholars within the cultural and scientific domains. Thus far, the majority of management scholars have tended to neglect love as a relevant topic of theorizing and research. Given the recent interest in the phenomenon in allied fields such as sociology and psychology, this is surprising. We create, inductively, an archetypical image of how managers make sense of the meaning of love as an organizational phenomenon by means of a sample of Christian managers. The findings indicate that such managers associate love with two core dimensions. First, they describe love as an expression of virtue. Second, they link love with a sense of community-ship. Organizational love can thus be theorized as the exercise of constructing virtuous, other-oriented human communities that transcend the productive functions of work and respond to important human needs, fulfilling normative performativity.